1990
DOI: 10.1002/jcb.240430107
|View full text |Cite
|
Sign up to set email alerts
|

Structure of O‐glycosidically linked oligosaccharides synthesized by the insect cell line Sf9

Abstract: The O-glycosidically linked oligosaccharides on the pseudorabies virus (PRV) glycoprotein gp50 synthesized by three different cell lines were studied. The intact membrane protein (gp50) was expressed in Vero cells and in the insect cell line Sf9. In addition, a truncated, secreted form lacking the transmembrane and cytoplasmic domains (gp50T), was expressed in CHO and Sf9 cells. The protein, both in intact and truncated form, synthesized by the two mammalian cells contained only the disaccharide Gal beta 1-3Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 37 publications
4
24
2
Order By: Relevance
“…Although we have not observed any differences between baculovirus and VEE-expressed Norwalk VLPs (Baric et al, submitted), previous experiments have demonstrated subtle variations between insect and mammalian posttranslational modification patterns of recombinant proteins (33,64). For example, baculovirus-and vaccinia virus-expressed papillomavirus VLPs were recently shown to possess notable variations in phosphorylation and glycosylation properties (19).…”
Section: Fig 5 Serum Igg Boost Responses From Nv1contrasting
confidence: 44%
“…Although we have not observed any differences between baculovirus and VEE-expressed Norwalk VLPs (Baric et al, submitted), previous experiments have demonstrated subtle variations between insect and mammalian posttranslational modification patterns of recombinant proteins (33,64). For example, baculovirus-and vaccinia virus-expressed papillomavirus VLPs were recently shown to possess notable variations in phosphorylation and glycosylation properties (19).…”
Section: Fig 5 Serum Igg Boost Responses From Nv1contrasting
confidence: 44%
“…Lectin analyses also show the presence of O-linked oligosaccharidic chains on recombinant subunits and eLH/CG secreted by Sf9 and Mimic TM cells, with a GalNAcGal disaccharide structure (Legardinier et al, submitted) as previously shown for insect or recombinant glycoproteins expressed in Sf9 and other insect cell lines [28,29].…”
Section: Biochemical Properties Of Recombinant Ecg Expressed In Baculsupporting
confidence: 54%
“…More recently, 0-linked glycosylation was also reported by several groups (Thomsen et al, 1990, Chen et al, 1991, Wathen et al, 1991, Svoboda et al, 1991.…”
mentioning
confidence: 58%